Group B Streptococcus Colonization in Pregnancy - BN Dissanayake; GC Herath; TM Gamage (Sri Lankan Journal of Infectious Diseases, 2015)
Introduction:  Group B β haemolytic streptococcus (GBS) is a colonizer of the female genital tract and a known cause of neonatal infections. Identification of GBS colonization in pregnancy is the key to prevent such infections. Published data regarding GBS colonization in pregnancy are limited in Sri Lanka. Objectives: The objectives of this study were to determine the prevalence of GBS colonization in pregnancy, to compare vaginal and rectal colonization rates and to find out the antibiotic susceptibility of the GBS isolates. Methods: Lower vaginal and rectal swabs were collected separately from 100 pregnant women of 35 to 37 weeks gestation attending the obstetric clinics at Teaching Hospital Peradeniya from August to November 2011. Vaginal and rectal swabs were separately enriched using Todd Hewitt broth supplemented with gentamicin and nalidixic acid and incubated at 35-37°C. Following overnight incubation, the enriched broth was subcultured onto blood agar. Suspected colonies were identified with Gram stain, catalase and Lancefield’s grouping. Susceptibility testing was performed using the Stokes method. Results: GBS colonization in the study sample was found to be 30%. GBS were recovered from both vaginal and rectal swabs in 20%. It was isolated only from vaginal swabs in 4% and only from rectal swabs in 6%. Rectal GBS colonization was 26% and higher than the vaginal colonization rate (24%). The sensitivity to penicillin was found to be 100% while the sensitivity to erythromycin and clindamycin were 63.3% and 30% respectively. Conclusion: This study implies the need for routine GBS screening in pregnancy and the importance of collecting both vaginal and rectal swabs for GBS screening.